2022
DOI: 10.3389/fpls.2022.733116
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Approach to Evaluate Durum Wheat–Faba Bean Mixed Crop Performance

Abstract: Plant breeding for intercropping is lagging because most varieties currently available in the market are selected for sole cropping systems. The present study analyzed the response of durum wheat (12 varieties) and faba bean (3 varieties) in pure and mixed cropping. Field trials were conducted in 2019 and 2020. The performance of each variety in mixed and pure cropping was evaluated using both univariate and multivariate analyses of the grain yield and land equivalent ratio (LER). For durum wheat, grain protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…On the research front, the performance of intercropping could be improved by the selection or breeding of crop varieties that are well suited to intercropping (Moore et al 2022(Moore et al , 2023. This is highlighted by the findings of Tavoletti and Merletti (2022) and Pankou et al (2022) on the performance of various varieties of durum wheat and faba bean or wheat and pea in intercropping. Consistently, Moutier et al (2022) found that both wheat and pea or faba bean variety had a significant impact on performance in an intercrop.…”
Section: Intercropping Future Research Needsmentioning
confidence: 98%
“…On the research front, the performance of intercropping could be improved by the selection or breeding of crop varieties that are well suited to intercropping (Moore et al 2022(Moore et al , 2023. This is highlighted by the findings of Tavoletti and Merletti (2022) and Pankou et al (2022) on the performance of various varieties of durum wheat and faba bean or wheat and pea in intercropping. Consistently, Moutier et al (2022) found that both wheat and pea or faba bean variety had a significant impact on performance in an intercrop.…”
Section: Intercropping Future Research Needsmentioning
confidence: 98%
“…The proper choice of the variety to be grown in intercropping is crucial because it deeply influences the performance of the whole combination ( Hauggaard-Nielsen and Jensen, 2001 ; Demie et al., 2022 ; Tavoletti and Merletti, 2022 ), and even though it has been reported that the performance of a plant grown as a sole crop is poorly correlated to its performance when grown in a mixture ( Annicchiarico et al., 2019 ) and despite the availability of genetic variability for intercropping ( Mouradi et al., 2018 ; El-Mehy et al., 2020 ; Tavoletti and Merletti, 2022 ), few studies aimed to select and develop CSFL varieties suitable for intercropping or to at least identify the traits associated with intercropping suitability.…”
Section: Cool-season Food Legumes In the Intercropping Systemmentioning
confidence: 99%
“…Given this present lack of genotypes suitable for mixing, the experiment of SW-FB crop mixture must rely on the SW cultivars available in the market which are selected for monocultures. Yet, it has been reported that the performance in sole crop could not be considered as an index of wheat performance in mixed cropping (Kammoun et al, 2021;Tavoletti & Merletti, 2022). The nal performance of intercropping depends on the combination of competition, complementarity, cooperation, and compensation between the species which has been named as "The 4C approach" (Demie et al, 2022;Justes et al, 2021).…”
Section: Dependence Mixture On Cultivar Identity Environment and Densitymentioning
confidence: 99%